Modified zinc acrylate resin, controllable self-polishing modified zinc acrylate resin-based marine antifouling coating and preparation method thereof
By introducing organic zinc complexes and nanoparticle modifiers into zinc acrylate resin, the release of zinc ions and the molecular structure of the resin is adjusted, and the problem of unstable self-polishing rate of existing anti-fouling paints is solved, achieving efficient and controllable anti-fouling performance and long-term stable coating performance in marine environments.
Patent Information
- Application Number
- CN202411982109.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing zinc acrylate resin-based self-polishing antifouling coatings have defects in self-polishing rate regulation, which is difficult to accurately adjust in different marine environments, resulting in the coating being polished prematurely in low-fouling sea areas or being polished too slowly in high-fouling areas, making it impossible to effectively prevent pollution.
Modified zinc acrylate resin, which includes monomers, functional monomer mixtures, nanoparticle modifiers and composite initiator systems synthesized by pre-reaction of organic zinc complexes, is used to adjust the self-polishing rate through the release of zinc ions, and improve the hardness and barrier properties of the coating through the nanoparticle modifier.
The self-polishing rate in seawater is stable and controllable, extends the service life of the coating, reduces the maintenance frequency of marine facilities such as ships, and achieves a good balance in hardness, flexibility, wear resistance, and pollution resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical materials, and in particular to a modified zinc acrylate resin, a controllable self-polishing modified zinc acrylate resin-based marine antifouling paint and a preparation method thereof. Background Art
[0002] In the marine environment, the surfaces of ships and marine engineering facilities are susceptible to fouling by algae, barnacles, mollusks and other organisms. Marine organisms attached to the parts of the hull below the waterline will increase the roughness of the hull surface, increase navigation resistance and fuel consumption, affect the maneuverability of the ship, and even cause instrument failure and sonar interference. At the same time, fouling organisms increase the weight of the hull, destroy the anti-corrosion coating, accelerate hull corrosion, reduce the strength of the hull structure, and increase the risk of maritime accidents. Therefore, antifouling paint is crucial in the marine field.
[0003] In recent years, self-polishing antifouling coatings have developed rapidly, among which zinc acrylate resin-based self-polishing antifouling coatings have great application potential. However, existing zinc acrylate resins have significant defects in regulating the self-polishing rate. Most traditional products are difficult to accurately adjust the self-polishing rate according to different marine environments and usage requirements, resulting in premature polishing of the coating in low-fouling waters, shortening the protection period; in high-fouling areas, the coating cannot be effectively polished due to slow polishing. In addition, the balance of the comprehensive properties of the resin, such as the coordination of hardness, flexibility, wear resistance and antifouling performance, has not yet reached an ideal state, making it difficult to meet the long-term protection needs of marine facilities in complex marine environments.
[0004] The zinc acrylate and silicon copolymer antifouling resin and its preparation method disclosed in the Chinese patent (CN201710587861.7) can regulate the hydrolysis rate and cost of the coating and have good environmental protection, but the comprehensive properties of the resin such as hardness and flexibility are not detailed, and there is a great need to optimize the monomer ratio in practical applications.
[0005] The preparation method of zinc acrylate resin and Wuxi self-polishing antifouling coating disclosed in the Chinese patent (CN113845615A) improves the synthesis efficiency and hydrolysis performance and has a good antifouling effect, but there is insufficient research on the precise control of the resin self-polishing rate and long-term stability, and the cuprous oxide antifouling agent used therein still has a certain environmental impact. Summary of the invention
[0006] In order to solve the problem that the polishing rate of the existing antifouling paint is fast in the early stage and slow in the later stage mentioned in the background technology, the present invention provides a modified acrylate zinc resin, which is characterized by comprising the following raw materials: The modified zinc acrylate monomer, the functional monomer mixture, the organic solvent, the initiator system and the nanoparticle modifier are prepared in a weight ratio of (8-12): (15-20): (25-35): (0.8-1.2): (3-5); The modified zinc acrylate monomer is synthesized by pre-reacting an organic zinc complex with acrylic acid at a molar ratio of 1:2 to 5; The functional monomer comprises a polylactic acid-based acrylate monomer and an acrylate monomer with a long-chain flexible spacer in a mass ratio of (3-8): (1-3). The nanoparticle modifier is composed of silicon dioxide nanoparticles with acrylate functional groups grafted on the surface and graphene oxide nanosheets in a mass ratio of (3-8):1; The initiator system is prepared by compounding a photoinitiator and a thermal initiator in a mass ratio of 1:(1-3).
[0007] In some embodiments, further, wherein the photoinitiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propanone (Darocur 1173), 1-hydroxy-cyclohexyl-phenyl ketone (Irgacure 184), and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO); The thermal initiator is one of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO) and dicumyl peroxide (DCP).
[0008] In some embodiments, further, the organic solvent is a solvent composed of cyclohexanone and xylene in a volume ratio of (1-3):(2-5).
[0009] In some embodiments, further, the preparation method of the modified zinc acrylate monomer is: In a reaction kettle, first add an organic solvent (such as toluene, xylene, etc., accounting for 30% to 50% of the total mass of the reaction system), then add the organic zinc complex, stir evenly and heat to 50 to 70°C; After the organic zinc complex is completely dissolved, slowly add acrylic acid, keep the temperature stable during the process, and react at 70-90°C for 3-5 hours, stirring continuously during the reaction to ensure that the reaction proceeds fully; After the reaction is completed, the solvent is removed by reduced pressure distillation or the like to obtain the modified zinc acrylate monomer.
[0010] In some embodiments, further, the organic zinc complex includes but is not limited to one of zinc acetylacetonate, dimethyl zinc, ethyl zinc, and diphenyl zinc.
[0011] The present invention also provides a method for preparing the modified zinc acrylate resin as described in any one of the preceding claims, comprising the following steps: Add the modified zinc acrylate monomer and the functional monomer mixture into the organic solvent, stir evenly under the protection of inert gas and heat to 65-75°C; Add the initiator system and perform photopolymerization for 1 to 2 hours with a light intensity of 10 to 50 mW / cm 2 , and then continue the thermal initiation polymerization reaction at 80-90°C for 3-4 hours; Add the nanoparticle modifier to the reaction system, stir and react at 70-80° C. for 1-2 hours to obtain the modified zinc acrylate resin.
[0012] The present invention also provides a controllable self-polishing modified zinc acrylate resin-based marine antifouling coating prepared by using the modified zinc acrylate resin as described above, comprising raw materials of the following components: 25-40 parts of modified acrylate zinc resin, 15-25 parts of solvent, 0.7-1.5 parts of thixotropic agent, 8-15 parts of composite antifouling agent, 5-15 parts of talc, 3-10 parts of titanium dioxide, 1-3 parts of red iron oxide, 0.4-0.8 parts of defoaming agent, and 0.8-1.5 parts of wetting and dispersing agent.
[0013] In some embodiments, further, the composite antifouling agent includes two or more of ECONEA, Zineb, DCOIT and benzisothiazolinone.
[0014] In some embodiments, further, the thixotropic agent is organic bentonite; The solvent is xylene; The defoamer is a polyether modified siloxane defoamer; The wetting and dispersing agent is a hyperbranched polyester dispersant.
[0015] In some embodiments, further, the following steps are included: Take the modified zinc acrylate resin, add it to the solvent, and stir it at a speed of 500 to 1000 rpm for 15 to 20 minutes until the modified zinc acrylate resin is completely dissolved to form a uniform modified zinc acrylate resin solution; Add thixotropic agent to the uniform modified zinc acrylate resin solution, stir at 800-1500 rpm for 5-15 minutes; slowly add composite antifouling agent, talcum powder, titanium dioxide and red iron oxide to the resin solution, add defoamer and wetting dispersant at the same time, stir at 1000-1500 rpm for 30-40 minutes; The coating viscosity is adjusted and filtered to obtain a controllable self-polishing modified acrylic zinc resin-based marine antifouling coating.
[0016] The principles and beneficial effects of the present invention are as follows: The technical solution of the present invention is to design and introduce an organic zinc complex into the zinc acrylate monomer in the modified zinc acrylate resin. The release characteristics of the zinc ions of the monomer synthesized by pre-reaction of the organic zinc complex with acrylic acid are one of the key factors for regulating the self-polishing rate. In a seawater environment, the release of zinc ions will induce chemical changes on the surface of the resin. Since zinc ions can react with components in seawater (such as carbonate ions, etc.) to form soluble compounds, the surface of the resin will slowly dissolve. Moreover, the structure of the organic zinc complex can regulate the release rate of zinc ions by changing factors such as its ligand environment.
[0017] By modifying zinc acrylate resin and applying it in antifouling coating, the self-polishing rate of coating in seawater is made more stable and controllable. The problem of fast polishing rate in the early stage and slow polishing rate in the later stage of existing antifouling coating is solved. It can maintain good antifouling performance for a long time, extend the service life of coating, and reduce the maintenance frequency of marine facilities such as ships.
[0018] In the preferred embodiment, the polylactic acid-based acrylate monomer and the acrylate monomer with a long-chain flexible spacer in the functional monomer mixture also have an important influence on the self-polishing rate. This combination not only gives the resin good flexibility and hydrolysis performance, but also improves the environmental friendliness of the resin to a certain extent, making it easier to degrade in the marine environment and reducing the long-term impact on the marine ecology; Preferably, an initiation system composed of a photoinitiator and a thermal initiator is used, and the polymerization is initiated by light first, and then by heat. This step-by-step initiation method can more accurately control the progress of the polymerization reaction and the molecular structure of the resin, thereby obtaining a modified zinc acrylate resin with better performance and narrower molecular weight distribution, which helps to improve the overall performance of the coating.
[0019] Furthermore, a nanoparticle modifier composed of silicon dioxide nanoparticles with surface grafted acrylate functional groups and graphene oxide nanosheets in a certain ratio is introduced. The addition of nanoparticles can significantly enhance the hardness, wear resistance and barrier properties of the resin, make the coating formed by the paint more dense, effectively block the intrusion of corrosive media such as seawater and oxygen, improve the anti-corrosion and anti-fouling properties of the coating, and also help improve the processing properties of the resin and the surface smoothness of the coating.
[0020] The controllable self-polishing modified acrylic zinc resin-based marine antifouling coating provided by the present invention achieves a good balance in hardness, flexibility, wear resistance, antifouling, etc. It has sufficient hardness to resist the attachment of marine organisms and the scouring of seawater, and has good flexibility to adapt to the deformation of marine facilities under dynamic conditions such as wave impact. At the same time, the improvement of wear resistance also makes the coating less prone to wear during long-term use, and always maintains a good protective effect. At the same time, its low VOC emissions and no release of toxic and harmful substances make its application in the marine environment more sustainable, which is in line with the current development trend of green environmental protection and is of great significance to the protection of the marine ecological environment. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] In the description of the present invention, it should be noted that all terms (including technical terms and scientific terms) used in the present invention have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and should not be understood as limitations on the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this invention.
[0023] The present invention provides the following modified acrylate zinc resin embodiments: Embodiment a Raw material preparation: accurately weigh 8 parts of modified zinc acrylate monomer (synthesized by pre-reaction of 10 parts (by mass ratio) of organic zinc complex zinc acetylacetonate and 30 parts of acrylic acid), 15 parts of functional monomer mixture (polylactic acid-based acrylate monomer and acrylate monomer with long-chain flexible spacer are mixed in a mass ratio of 3:2), 25 parts of combined solvent of cyclohexanone and xylene (cyclohexanone and xylene ratio is 1:3). Darocur 1173 is used as the photoinitiator, azobisisobutyronitrile (AIBN) is used as the thermal initiator, and 0.8 parts of the initiator system (photoinitiator and thermal initiator are mixed in a ratio of 1:2) and 3 parts of nanoparticle modifier (silicon dioxide nanoparticles with surface grafted acrylate functional groups and graphene oxide nanosheets are composed of a ratio of 5:1).
[0024] Preparation process: Add the weighed modified zinc acrylate monomer and functional monomer mixture into the organic solvent, stir at 300 rpm for 15 minutes under nitrogen protection to make it evenly mixed, and then heat to 65°C. Then add the initiator system, first carry out 1 hour of photoinitiated polymerization, during which the light intensity range is controlled at 30 mW / cm². Then continue the thermal initiation polymerization at 80°C for 3 hours, and keep the temperature of the reaction system stable within the range of ±2°C during the thermal initiation process. Finally, add the nanoparticle modifier to the reaction system, stir and react at 70°C at 400 rpm for 1 hour to obtain the modified zinc acrylate resin.
[0025] Wherein, the preparation method of modified zinc acrylate monomer is: According to the proportion, first add the organic solvent (toluene, accounting for 40% of the total mass of the reaction system) into the reaction kettle, then add the organic zinc complex, stir evenly and heat to 50-70°C; After the organic zinc complex is completely dissolved, acrylic acid is slowly added, the temperature is kept stable during the process, and the reaction is carried out at 70-90° C. for 4 hours, and stirring is continued during the reaction to allow the reaction to proceed fully. After the reaction is completed, the solvent is removed by reduced pressure distillation or the like to obtain a modified zinc acrylate monomer.
[0026] Embodiment b Raw material preparation: Weigh 10 parts of modified zinc acrylate monomer (same as in Example a), 18 parts of functional monomer mixture (same as in Example a), 30 parts of cyclohexanone and xylene combined solvent (the ratio of cyclohexanone to xylene is adjusted to 2:5). The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), the thermal initiator is benzoyl peroxide (BPO), 1.0 part of the initiator system (the ratio of photoinitiator to thermal initiator is 1:1), and 4 parts of nanoparticle modifier (the ratio of silica nanoparticles and graphene oxide nanosheets with surface grafted acrylate functional groups is 4:1.
[0027] Preparation process: Add the monomer and mixture to the solvent, stir for 20 minutes under argon protection until uniform, rotate at 350 rpm, and heat to 70°C. Add the initiator system, photoinitiate for 1.5 hours (the light intensity of the photoinitiator is set to 40 mW / cm², and then thermally initiate polymerization at 85°C for 3.5 hours, with a temperature control accuracy of ±1.5°C. Finally, add the nanoparticle modifier, stir at 75°C and 450 rpm for 1.5 hours to obtain the modified zinc acrylate resin.
[0028] Example c Raw material preparation: prepare 12 parts of modified zinc acrylate monomer (same as Example a), 20 parts of functional monomer mixture (same as Example a), 35 parts of cyclohexanone and xylene combined solvent (cyclohexanone and xylene ratio is 8:1). The photoinitiator is 1-hydroxy-cyclohexyl-phenyl ketone (Irgacure 184), the thermal initiator is diisopropylbenzene peroxide (DCP), weigh 1.2 parts of initiator system (the ratio of photoinitiator to thermal initiator is 2:3), and 5 parts of nanoparticle modifier (silicon dioxide nanoparticles and graphene oxide nanosheets with surface grafted acrylate functional groups are in a ratio of 8:1).
[0029] Preparation process: Add the raw materials to the solvent, stir at 400 rpm for 25 minutes under helium protection, and then heat to 75°C. Add the initiator system, photoinitiate for 2 hours (the light intensity of the photoinitiator is set to 20 mW / cm²), then thermally initiate polymerization at 90°C for 4 hours, and control the temperature fluctuation within ±1°C. Finally, add the nanoparticle modifier, stir at 80°C and 500 rpm for 2 hours to obtain the modified zinc acrylate resin.
[0030] The present invention also provides a controllable self-polishing modified acrylic zinc resin-based marine antifouling coating embodiment Example 1 Raw material preparation: Take 25 parts of the modified zinc acrylate resin prepared in Example a above, 15 parts of xylene, 0.7 parts of organic bentonite thixotropic agent, 8 parts of composite antifouling agent (ECONEA and mancozeb mixed in a ratio of 1:1), 5 parts of talc, 3 parts of titanium dioxide, 1 part of red iron oxide, 0.4 parts of polyether modified siloxane defoaming agent, and 0.8 parts of hyperbranched polyester dispersant.
[0031] Preparation process: Add modified zinc acrylate resin to xylene and stir at 500 rpm for 15 minutes until the resin is completely dissolved to form a uniform resin solution. Then add thixotropic agent and stir at 800 rpm for 5 minutes. Then slowly add composite antifouling agent, talcum powder, titanium dioxide and red iron oxide to the resin solution, add defoamer and wetting dispersant at the same time, and stir at 1000 rpm for 30 minutes. Finally, adjust the viscosity of the coating to 6000-12000 mPa·s with the remaining xylene, and filter through a 200-mesh filter to obtain the finished antifouling coating.
[0032] Example 2 Raw material preparation: weigh 32 parts of the modified zinc acrylate resin obtained in Example b, 20 parts of xylene, 1.0 part of organic bentonite thixotropic agent, 12 parts of composite antifouling agent (DCOIT and benzisothiazolinone mixed in a ratio of 1:1), 10 parts of talc, 6 parts of titanium dioxide, 2 parts of red iron oxide, 0.6 parts of polyether modified siloxane defoaming agent, and 1.2 parts of hyperbranched polyester dispersant.
[0033] Preparation process: Add xylene to the resin and stir at 600 rpm for 18 minutes to dissolve into solution, add thixotropic agent and stir at 1000 rpm for 10 minutes, add the remaining materials and additives and stir at 1200 rpm for 35 minutes, adjust the viscosity to 6000-10000 mPa·s with the remaining xylene, and filter through a 250-mesh filter to obtain the finished product.
[0034] Example 3 Raw material preparation: 40 parts of modified acrylate zinc resin prepared in Example c, 25 parts of xylene, 1.5 parts of organic bentonite thixotropic agent, 15 parts of composite antifouling agent (ECONEA, DCOIT and mancozeb mixed in a ratio of 1:1:1), 15 parts of talc, 10 parts of titanium dioxide, 3 parts of red iron oxide, 0.8 parts of polyether modified siloxane defoaming agent, and 1.5 parts of hyperbranched polyester dispersant.
[0035] Preparation process: Modified zinc acrylate resin is dissolved in xylene, stirred at 700 rpm for 20 minutes to form a solution, thixotropic agent is added and stirred at 1200 rpm for 15 minutes, various components and additives are added and stirred at 1500 rpm for 40 minutes, the viscosity is adjusted to 6000-10000 mPa·s with xylene, and the coating is filtered through a 300-mesh filter to obtain the finished product.
[0036] During the preparation process of each embodiment, the ambient temperature must be strictly controlled at 23°C ± 2°C and the humidity must be controlled at 40% to 60% to ensure the consistency and stability of the experimental conditions and reduce the impact of environmental factors on the experimental results.
[0037] The present invention also provides the following comparative examples Comparative Example 1: No organic zinc complex was introduced into the zinc acrylate monomer.
[0038] Coating formula: Compared with Example 1, ordinary zinc acrylate is used to replace the acrylic monomer introduced with the organic zinc complex; the other conditions are consistent with Example 1.
[0039] Comparative Example 2: Zinc acrylate resin-based marine antifouling coating with only the initiator system changed Coating formula: Compared with Example 1, the initiator system in the modified zinc acrylate resin only uses a single thermal initiator azobisisobutyronitrile (AIBN) and no photoinitiator, and the other conditions remain the same as in Example 1.
[0040] Comparative Example 3: Marine antifouling coating based on zinc acrylate resin without functional monomer Coating formula: Compared with Example 1, the modified zinc acrylate resin does not contain polylactic acid-based acrylate monomers and acrylate monomers with long-chain flexible spacer groups, and the other conditions remain the same as in Example 1.
[0041] Comparative Example 4: Marine antifouling coating based on acrylic zinc resin without nanoparticle modification Coating formula: Compared with Example 1, the modified zinc acrylate resin is used, and no nanoparticle modifier is added. The other conditions are the same as those in Example 1.
[0042] The coatings prepared in the examples of the present invention and the comparative examples were tested according to the performance indicators described in Table 1: Table 1 project Technical indicators Detection Methods Adhesion ≥3 MPa GB / T 5210 Coating hardness ≥H GB / T 6739 Flexibility Cylindrical shaft bending test (bending diameter 1-3mm) without cracks or peeling GB / T 1731 Wear resistance Taber wear tester (load 500 g ~ 1000 g, 1000 ~ 2000 revolutions) wear loss <0.05 g GB / T 1768 Salt water resistance No blistering, rusting or shedding GB / T 1083 Salt spray resistance, >2000h No obvious corrosion GB / T 10125 Shallow sea immersion (3 peak seasons for marine organisms), score Biological coverage score ≥85, area ≤10% GB / T 5370 Dynamic simulation test, 8 cycles, scoring Biological coverage score ≥85, area ≤10% GB / T 7789 Total copper, % ≤2 GB / T 6822 Surface drying time (23℃±2℃), h ≤3 GB / T 1728 Drying time (23℃±2℃), h ≤24 GB / T 1728 Storage stability conform to GB / T 6753 The technical test results are shown in Table 2: Table 2
[0043] It can be seen from the above embodiments and comparative examples that the antifouling coating provided by the technical solution of the present invention makes the self-polishing rate of the coating in seawater more stable and controllable by modifying the zinc acrylate resin and optimizing the coating formula. The problem of the existing antifouling paint having a fast polishing rate in the early stage and a slow polishing rate in the later stage is solved, and good antifouling performance can be maintained for a long time, the service life of the coating is extended, and the maintenance frequency of marine facilities such as ships is reduced.
[0044] In addition, a good balance is achieved in terms of hardness, flexibility, wear resistance, antifouling, etc. It has sufficient hardness to resist the attachment of marine organisms and the scouring of seawater, and good flexibility to adapt to the deformation of marine facilities under dynamic conditions such as wave impact. At the same time, the improvement of wear resistance also makes the coating less likely to wear during long-term use, and always maintains a good protective effect.
[0045] More specifically, the technical solution of the present invention introduces an organic zinc complex into the acrylic monomer in the modified zinc acrylate resin. The release characteristics of the zinc ions of the monomer synthesized by pre-reaction of the organic zinc complex with acrylic acid are one of the key factors for regulating the self-polishing rate. In a seawater environment, the release of zinc ions will trigger chemical changes on the surface of the resin. Since zinc ions can react with components in seawater (such as carbonate ions, etc.) to form soluble compounds, the surface of the resin will slowly dissolve. Moreover, the structure of the organic zinc complex can regulate the release rate of zinc ions by changing factors such as its ligand environment. For example, the steric hindrance and electronic effect of the ligand will affect the reactivity of zinc ions with external substances. If the steric hindrance of the ligand is small and the electron donation ability to the zinc ion is moderate, the zinc ion will react more easily with the components in the seawater, thereby accelerating the self-polishing rate of the resin; otherwise, the self-polishing rate will slow down.
[0046] By modifying zinc acrylate resin and applying it in antifouling coating, the self-polishing rate of coating in seawater is made more stable and controllable. The problem of fast polishing rate in the early stage and slow polishing rate in the later stage of existing antifouling coating is solved. It can maintain good antifouling performance for a long time, extend the service life of coating, and reduce the maintenance frequency of marine facilities such as ships.
[0047] The polylactic acid-based acrylate monomer and the acrylate monomer with a long-chain flexible spacer in the functional monomer mixture also have an important influence on the self-polishing rate. The polylactic acid-based acrylate monomer is biodegradable, and its degradation process in the seawater environment will change the surface structure of the resin. The acrylate monomer with a long-chain flexible spacer can regulate the flexibility and hydrolysis rate of the resin. The long-chain structure can hinder the contact between water molecules and the internal chemical bonds of the resin to a certain extent. When the content or length of the long-chain structure changes, the hydrolysis rate of the resin will also change. Specifically, increasing the content of the long-chain flexible spacer acrylate monomer will partially shield the hydrolysis site of the resin, making it more difficult for water molecules to reach the reactive active sites, thereby reducing the hydrolysis rate of the resin and slowing down the self-polishing process.
[0048] In addition, the nanoparticle modifier is composed of silica nanoparticles and graphene oxide nanosheets with surface grafted acrylate functional groups, which plays a vital role in improving the comprehensive performance of the coating. Silica nanoparticles can significantly enhance the hardness and wear resistance of the resin, and their dispersion state and content in the resin have a profound impact on the surface microstructure of the resin. When the silica nanoparticles are evenly dispersed and the content is in an appropriate range, an effective physical protective barrier will be formed on the surface of the resin, significantly slowing down the erosion rate of the resin by seawater. Graphene oxide nanosheets, with their unique two-dimensional sheet structure, greatly improve the barrier properties of the resin, and can effectively prevent corrosive substances and microorganisms in seawater from contacting the chemical bonds inside the resin. The nanoparticle modifier composed of silica nanoparticles and graphene oxide nanosheets with surface grafted acrylate functional groups can greatly increase the density of the resin surface by stacking layers, reduce the penetration of water molecules and other active substances, thereby reducing the hydrolysis rate of the resin, indirectly regulating the self-polishing rate, and then synergizing with other components in the coating to optimize the overall performance of the coating.
[0049] In the preparation process of resin, the initiation system composed of photoinitiator and thermal initiator in a specific ratio is the key element. The photoinitiator will quickly start the surface polymerization reaction at the beginning of the reaction, prompting the reaction to unfold quickly; while the thermal initiator will continue to provide stable and lasting power for the polymerization process in the subsequent stage to ensure the integrity and continuity of the entire polymerization reaction. By adjusting the key parameters such as time and intensity during the photoinitiation and thermal initiation process, the structural characteristics such as the length, branching degree and cross-linking density of the resin molecular chain can be effectively changed. For example, when the photoinitiation time is appropriately extended, the molecular chains on the surface of the resin will present a more regular and tight arrangement state, forming a denser surface structure. This structural change will effectively reduce the erosion rate of seawater on the resin, and then inhibit the self-polishing rate. At the same time, the change in molecular structure will further affect the stability of the chemical bonds inside the resin, play a decisive role in the hydrolysis and dissolution process in the seawater environment, and ultimately achieve accurate and effective regulation of the self-polishing rate.
[0050] The antifouling coating of the present invention exhibits excellent comprehensive performance. Its core component, modified zinc acrylate resin, has a unique synergistic effect with the environmentally friendly antifouling agent, and exhibits excellent inhibition and killing capabilities against various fouling organisms including algae and barnacles, thereby significantly extending the antifouling cycle. Through a carefully designed structure and component combination, the coating can accurately and stably adjust the self-polishing rate in different complex marine application scenarios. The antifouling paint is suitable for a variety of marine environments and facilities, including ships, offshore platforms, underwater pipelines and marine energy facilities, and has broad market application potential. It exhibits excellent comprehensive performance in terms of environmental protection, antifouling effect, mechanical properties and economic benefits, meeting the needs of the modern marine industry for high-performance and environmentally friendly coatings.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. In the embodiments and comparative examples, common raw materials and preparation parameters not mentioned can be selected by those skilled in the art according to the design ideas of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some or all of the technical features therein. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified zinc acrylate resin, characterized in that: Including the following ingredients: The modified zinc acrylate monomer, the functional monomer mixture, the organic solvent, the initiator system and the nanoparticle modifier are prepared in a weight ratio of (8-12): (15-20): (25-35): (0.8-1.2): (3-5); The modified zinc acrylate monomer is synthesized by pre-reacting an organic zinc complex with acrylic acid at a molar ratio of 1:(2-5); The functional monomer is composed of a polylactic acid-based acrylate monomer and an acrylate monomer with a long-chain flexible spacer in a mass ratio of (3-8): (1-3). The nanoparticle modifier is composed of silicon dioxide nanoparticles with acrylate functional groups grafted on the surface and graphene oxide nanosheets in a mass ratio of (3-8):1; The initiator system is prepared by compounding a photoinitiator and a thermal initiator in a mass ratio of 1:(1-3).
2. The modified acrylate zinc resin according to claim 1, characterized in that: in, The photoinitiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl-phenyl ketone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; The thermal initiator is one of azobisisobutyronitrile, benzoyl peroxide and dicumyl peroxide.
3. The modified acrylate zinc resin according to claim 1, characterized in that: The organic solvent is a solvent composed of cyclohexanone and xylene in a volume ratio of (1-3):(2-5).
4. The modified acrylate zinc resin according to claim 1, characterized in that: The preparation method of the modified zinc acrylate monomer is: In the reaction kettle, first add the organic solvent, then add the organic zinc complex. Stir well and heat to 50-70℃; After the organic zinc complex is completely dissolved, slowly add acrylic acid, keep the temperature stable during the process, and react at 70-90°C for 3-5 hours, stirring continuously during the reaction to ensure that the reaction proceeds fully; After the reaction is completed, the solvent is removed by reduced pressure distillation or the like to obtain the modified zinc acrylate monomer.
5. The modified acrylate zinc resin according to claim 1, characterized in that: The organic zinc complex includes, but is not limited to, one of zinc acetylacetonate, dimethyl zinc, ethyl zinc, and diphenyl zinc.
6. A method for preparing the modified zinc acrylate resin according to any one of claims 1 to 5, characterized in that: The following steps are involved: Add the modified zinc acrylate monomer and the functional monomer mixture into the organic solvent, stir evenly under the protection of inert gas and heat to 65-75°C; Add the initiator system and perform photopolymerization for 1 to 2 hours with a light intensity of 10 to 50 mW / cm 2 , and then continue the thermal initiation polymerization reaction at 80-90°C for 3-4 hours; Add the nanoparticle modifier to the reaction system, stir and react at 70-80° C. for 1-2 hours to obtain the modified zinc acrylate resin.
7. A controllable self-polishing modified zinc acrylate resin-based marine antifouling coating prepared using the modified zinc acrylate resin according to any one of claims 1 to 5, characterized in that: The raw materials include the following components: 25-40 parts of modified acrylate zinc resin, 15-25 parts of solvent, 0.7-1.5 parts of thixotropic agent, 8-15 parts of composite antifouling agent, 5-15 parts of talc, 3-10 parts of titanium dioxide, 1-3 parts of red iron oxide, 0.4-0.8 parts of defoaming agent, and 0.8-1.5 parts of wetting and dispersing agent.
8. The controllable self-polishing modified acrylic zinc resin-based marine antifouling paint according to claim 1, characterized in that: The composite antifouling agent comprises two or more of ECONEA, Zineb, DCOIT and benzisothiazolinone.
9. The controllable self-polishing modified acrylic zinc resin-based marine antifouling paint according to claim 1, characterized in that: The thixotropic agent is organic bentonite; The solvent is xylene; The defoamer is a polyether modified siloxane defoamer; The wetting and dispersing agent is a hyperbranched polyester dispersant.
10. The method for preparing the controllable self-polishing modified acrylate zinc resin-based marine antifouling coating according to claim 1, characterized in that: The following steps are involved: Take the modified zinc acrylate resin, add it to the solvent, and stir it at a speed of 500 to 1000 rpm for 15 to 20 minutes until the modified zinc acrylate resin is completely dissolved to form a uniform modified zinc acrylate resin solution; Add thixotropic agent to the uniform modified zinc acrylate resin solution, stir at 800-1500 rpm for 5-15 minutes; slowly add composite antifouling agent, talcum powder, titanium dioxide and red iron oxide to the resin solution, add defoamer and wetting dispersant at the same time, stir at 1000-1500 rpm for 30-40 minutes; The coating viscosity is adjusted and filtered to obtain a controllable self-polishing modified acrylic zinc resin-based marine antifouling coating.
Citation Information
Patent Citations
Head, neck and shoulder acupoint adjustment positioning apparatus
CN107320325A
Zinc acrylate resin and preparation method of tin-free self-polishing antifouling coating containing zinc acrylate resin
CN113845615A
Cited By
Super anti-corrosion powder coating for marine facilities and preparation method of super anti-corrosion powder coating
CN122080725A